Integration of trap‐ and root‐derived nitrogen nutrition of carnivorous Dionaea muscipula. Issue 3 (27th October 2014) - Gao, Peng; Loeffler, Theresa Sofi; Honsel, Anne; Kruse, Jörg; Krol, Elzbieta; Scherzer, Sönke; Kreuzer, Ines; Bemm, Felix; Buegger, Franz; Burzlaff, Tim; Hedrich, Rainer; Rennenberg, Heinz
Summary: Carnivorous Dionaea muscipula operates active snap traps for nutrient acquisition from prey; so what is the role of D. muscipula 's reduced root system? We studied the capacity for nitrogen (N) acquisition via traps, and its effect on plant allometry; the capacity of roots to absorb NO3 −, NH4 + and glutamine from the soil solution; and the fate and interaction of foliar‐ and root‐acquired N. Feeding D. muscipula snap traps with insects had little effect on the root : shoot ratio, but promoted petiole relative to trap growth. Large amounts of NH4 + and glutamine were absorbed upon root feeding. The high capacity for root N uptake was maintained upon feeding traps with glutamine. High root acquisition of NH4 + was mediated by 2.5‐fold higher expression of the NH4 + transporter DmAMT1 in the roots compared with the traps. Electrophysiological studies confirmed a high constitutive capacity for NH4 + uptake by roots. Glutamine feeding of traps inhibited the influx of 15 N from root‐absorbed 15 N/ 13 C‐glutamine into these traps, but not that of 13 C. Apparently, fed traps turned into carbon sinks that even acquired organic carbon from roots. N acquisition at the whole‐plant level is fundamentally different in D. muscipula compared with noncarnivorous species, where foliar N influx down‐regulates N uptake by roots.